Państwa Kaukazu Południowego w wypowiedziach rzeczniczki prasowej Ministerstwa Spraw Zagranicznych Federacji Rosyjskiej (Politeja, 2022)
STATES OF THE SOUTH CAUCASUS IN THE STATEMENTS OF THE PRESS SPOKESWOMAN OF THE MINISTRY OF FOREIGN AFFAIRS OF THE RUSSIAN FEDERATIONThe Russian Federation currently plays a key role in the South Caucasus region. The aim of the article is to attempt to answer the question of how and to what extent Armenia, Azerbaijan and Georgia are present in the message presented by the Russian Ministry of Foreign Affairs. The briefings of the spokesperson of the Ministry of Foreign Affairs of the Russian Federation, which took place between July and December 2020, i.e. during events important for the region, were subject to quantitative and qualitative analysis. The South Caucasus, in the light of the spokesperson’s statements, is not a priority for the Russian diplomatic service, but as a result of the foreign policy it is creating, it appears relatively regularly. The key topics in the analyzed period include the COVID-19 pandemic and the new phase of the conflict over Nagorno-Karabakh. The thought-out narrative of the Russian Ministry of Foreign Affairs, which served to shape the perception of the region and strengthen the Russian position, should be emphasized.